Burnout, perceived stress, and empathic concern: differences in female and male Millennial medical students. Issue 4 (21st April 2019) - Worly, Brett; Verbeck, Nicole; Walker, Curt; Clinchot, Daniel M
ABSTRACT: The 'Millennial' generation faces medical education learning environment challenges differently. We explore gender differences in burnout, perceived stress, and empathic concern in third-year medical students. A sample size of 654 third-year medical students completed an annual survey over 6 years. Survey items included: the Maslach Burnout Inventory-Student Scale (MBI-SS), Interpersonal Reactivity Index (IRI), and Perceived Stress Scale (PSS). We examined demographic differences using independent sample t-tests and performed a two-way ANOVA to test for potential interactions. Female students were more likely to have higher empathic concern compared to male students (IRI) (20.9±3.9 versus 19.1±4.1, p<0.001), and reported more personal distress (IRI) (9.0±4.4 versus 7.6±3.8, p<0.001), emotional exhaustion (MBI-SS) (15.6±5.9 versus 14.4±5.9, P<0.013), and perceived stress (PSS) (17.3±6.1 versus 15.2±6.7, p<0.001). Male students were more likely to have cynicism (MBI-SS) and lower professional efficacy (MBI-SS) scores. Results of multivariate analyses yielded no significant interactions between gender, age, and ethnicity. Self-reported experiences of burnout and stress differed in male and female third-year medical students. Burnout and perceived stress scores while statistically significant were small. These findings suggest that support services should be made broadly available to all medical students, but should be targeted to the specific needs of male and female students.